Facebook Enhances Antidepressant Pharmacotherapy Effects - Jorge Mota Pereira (The Scientific World Journal)
Treatment-resistant major depressive disorder (TR-MDD) is a complex condition, with very low remission rates. In recent years some studies have been conducted on the implementation of cognitive behavioral therapy and psychodynamic psychotherapy interventions via the Internet to MDD patients, and results have been promising. However, there have been no studies in patients with TR-MDD nor with the use of Facebook with the psychiatrist as “friend.” 60 TR-MDD patients were randomized to one of three groups: Facebook group with psychiatrist as “friend,” Facebook group without psychiatrist as “friend,” and control group (no Facebook use). Both Facebook groups spent at least 1 hour/day on Facebook, 7 days/week, during the 3 months. All patients maintained their usual pharmacotherapy. All participants were evaluated at baseline and at 1, 2, and 3 months for depressive symptoms using HAD17 and BDI-II. Results show that both Facebook groups had a decrease on HADM17 and BDI-II scores as well as higher remission and response rates than the control group, with better results if the psychiatrist was a “friend” on Facebook. Therefore, in TR-MDD, Facebook can be used as an effective enhancement therapy, adjuvant to pharmacological therapy with regular consultations, especially if the psychiatrist is the patient’s online “friend.”